Growth Performance, Fasting Plasma Glucose and Lipid Profile of Sprague-Dawley Rats Fed Different Levels of Omani Halwa - Ali, Amanat; Al-Zuhaibi, Khalid M.; Waly, Mostafa I.; Sankar, D.; Johnson, Eugene H. (Pakistan Journal of Nutrition, 2015)
Omani halwa is a traditional sweet delicacy. The present study evaluated the effects of feeding different levels of Omani halwa on the growth performance, fasting plasma glucose, glycated hemoglobin (HbA1c) and plasma lipid profile of Sprague-Dawley rats. Forty two, 4 weeks old male SD-rats were randomly divided into 7 groups containing 6 rats in each. Six experimental diets, (in which the normal rat chow was replaced with either white or black Omani halwa at 10, 15 and 20% level), were prepared and fed for 10 weeks. The group fed on rat chow acted as control. No significant (p<0.05) differences were observed in the feed consumption and growth performance of rats fed diets containing different levels and types of halwa. Significant (p<0.05) differences were observed in fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) values in rats fed different experimental diets. Diets containing 20% of halwa showed significantly (p<0.05) higher FPG and HbA1c values. Similarly the rats fed diets containing 20% of halwa showed significantly (p<0.05) higher lipid profile i.e., TC, TG, HDL-C and LDL-C values as compared to control. However, the TC/HDL-C ratio did not differ significantly (p>0.05). The plasma creatinine levels differed significantly (p<0.05) whereas the plasma albumin levels did not differ (p>0.05) in rats fed various experimental diets. Feeding Omani halwa at 15% level in diets did not affect (p>0.05) the growth, fasting plasma glucose, glycated hemoglobin (HbA1c) and lipid profile of rats.